Methods of preparation in conservation of minimally processed products of Cactus Pear Fruits - Marques, Kelly Magalhães [UNESP]; Mattiuz, Ben-Hur [UNESP]; Morgado, Cristiane Maria Ascari [UNESP]; Galati, Vanessa Cury [UNESP]; Miguel, Ana Carolina Almeida [UNESP] (FapUNIFESP (SciELO), 2011)
The objective of this study was to evaluate the influence of methods of preparation in postharvest conservation of minimally processed products of cactus pear fruits. Ripe cactus pear fruits orangefleshed, from a commercial orchard in the region of Valinhos, SP, Brazil, were used. After selection, the fruits were washed and the surface sanitized with a solution of dichloro s. triazinatriona sodium dihydrate (Sumaveg®) 200 mg 100g-1 of free chlorine for 5 minutes. Fruits were then stored at 12°C for 12 hours before processing. The first process was the removal of the shell and ends. Then, the fruits were cut longitudinally into two halves, peeled and sliced in 2 cm thick cross-sections. The whole fruit, halves and slices were packaged in polyethylene terephthalate containers (Neoforma® N-94). These units were stored at 3°C for 16 days and analyses were performed every 4 days. The weight loss, the content of soluble solids (SS), the titratable acidity (TA), the ratio (SS / TA) and the ascorbic acid content were evaluated and the sensory analysis of products was performed. Whole fruits were preferred concerning the purchase intent and showed better results regarding the content of soluble solids, titratable acidity, soluble solids / titratable acidity and ascorbic acid content. The highest weight loss was observed in slices.
Formas de Preparo de Figo-da-Índia Minimamente Processado
Keywords: Minimally processed; Opuntia fícus indica; Postharvest